2001
DOI: 10.1097/00006123-200112000-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Size and Location of Ruptured Intracranial Aneurysms

Abstract: We argue that the risk of small aneurysms rupturing is not insignificant, especially those of the anterior communicating artery. Our findings indicate that surgery on unruptured aneurysms should not be predicated on aneurysm size alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
171
4
16

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(207 citation statements)
references
References 10 publications
16
171
4
16
Order By: Relevance
“…Nevertheless, the majority of ruptured and unruptured aneurysms are still < 7 mm, and a substantial percentage of ruptured aneurysms are even < 5 mm. 11,27,28 Thus, aneurysm size and location appear to be insufficient single parameters to guide treatment decisions, but they can at least serve as a guide for higher risk lesions.…”
Section: 40mentioning
confidence: 99%
“…Nevertheless, the majority of ruptured and unruptured aneurysms are still < 7 mm, and a substantial percentage of ruptured aneurysms are even < 5 mm. 11,27,28 Thus, aneurysm size and location appear to be insufficient single parameters to guide treatment decisions, but they can at least serve as a guide for higher risk lesions.…”
Section: 40mentioning
confidence: 99%
“…Some factors, such as hypertension, arteriosclerosis, intrinsic disorders of the vessel wall, contraceptive use, and trauma can predispose to true PCoA aneurysms. Several studies have reported that PCoA and anterior communicating artery aneurysms are more prone to rupture than aneurysms in other parts (2,3,4,5). In the analysis of the available information from the included case reports and case series, 44 of 49 (89.8%) "true" PCoA aneurysms were ruptured, demonstrating that true posterior communicating artery aneurysms are more prone to rupture (6,14).…”
Section: Discussionmentioning
confidence: 97%
“…In other studies, a significant part of ruptured IAs are small [8,9]. Intracranial aneurysm size is a widely used measurement for rupture risk assessment, but it may miss smaller aneurysms that have a higher rupture risk based on some other characteristics lake location or relationship with the parent blood vessel [10].…”
Section: Discussionmentioning
confidence: 99%